Increasing radiation doses in Anastrepha obliqua (Diptera: Tephritidae) larvae improve parasitoid mass-rearing attributes. Issue 6 (28th December 2022) - Cancino, Jorge; Ayala, Amanda; Ríos, Laura; López, Patricia; Suárez, Lorena; Ovruski, Sergio M.; Hendrichs, Jorge
Abstract: Doses of 40, 80, 120, and 160 Gy were applied to 5-, 6-, 7-, and 8-day-old Anastrepha obliqua larvae, which were exposed to the Neotropical-native braconids Doryctobracon crawfordi and Utetes anastrephae and the Asian braconid Diachasmimorpha longicaudata . These tests were performed to know the effect of the increase in host radiation on the emergence of the aforementioned parasitoids and the related consequences of oviposition on the host. The study was based on the fact that higher radiation doses may cause a decrease in the host immune activity. There was a direct relationship between the increase in radiation dose and the parasitoid emergence. Both, the weight and the mortality of the host larvae were not affected by radiation. Although the larval weight of the larvae was lower and the mortality was higher in the younger larvae. Both, the number of scars and immature stages per host puparium originated from the younger larvae were lower than those from older larvae. Only U. anastrephae superparasitized more at lower radiation. Superparasitism by D. longicaudata was more frequent at 160 Gy. Qualitative measurements of melanin in the larvae parasitized showed that the levels were lower with increasing radiation. As radiation doses increased, the antagonistic response of the A. obliqua larva was reduced. Host larvae aged 5- and 6-day-old irradiated at 120–160 Gy significantly improve parasitoid emergence. This evidence is relevant for the mass production of the three tested parasitoid species.